Assessment of skin basement membrane zone antibodies in the urine of patients with acquired subepidermal immunobullous diseases. - Allen, J; Shears, E; Powell, J; Wojnarowska, F (2001)
BACKGROUND: In bullous pemphigoid (BP), cicatricial pemphigoid (CP) and linear IgA disease (LAD), autoantibodies to the basement membrane zone (BMZ) are found in skin and mucosa, blood and blister fluid. OBJECTIVES: To assess whether BMZ antibodies might also be detected in urine. METHODS: Urine and serum samples from 62 patients (32 with BP, 17 with CP and 13 with LAD) were analysed for antibody isotypes and subclasses by indirect immunofluorescence, and urine and serum samples from 40 patients (25 with BP, eight with CP and seven with LAD) were screened for target antigens using immunoblotting. RESULTS: Fourteen of 32 patients with BP had detectable levels of IgG BMZ autoantibodies in their urine, and all 32 had positive sera. Of these 14 BP patients, 13 had epidermal-binding serum autoantibodies at a titre > 1 : 160, and one had dermal-binding serum antibodies at a titre of 1 : 40. BMZ autoantibodies were not detected in the urine of the CP or LAD patients, but the corresponding sera were of low titre or negative. IgG subclasses (IgG1-4) were less frequently detected in urine than in serum. IgG4 was the predominant subgroup found (10 urine samples and all 14 sera), followed by IgG1 (two urine samples and 12 sera); IgG2 was detected in a single urine sample and three sera, and IgG3 was not detected. Eight of 25 BP and one of eight CP urine samples were positive on immunoblotting, and bound BP230 and/or BP180 with IgA and/or IgG autoantibodies. IgA autoantibodies were not detected in the urine of the seven LAD patients. The corresponding sera were often more positive, with 21 of 25 BP, five of eight CP and six of seven LAD sera immunoblotting the major BP antigens. CONCLUSIONS: The detection of IgG autoantibodies from urine samples using indirect immunofluorescence correlated with a high titre of IgG autoantibodies in the serum. IgG and IgA autoantibodies in the urine were detected by immunoblotting, although less frequently than in serum. The finding of BMZ antibodies in the urine of many BP patients may have clinical relevance, and may have a restricted application in the diagnosis of immunobullous disease.